STATE PROPERTY: ECONOMIC ANALYSIS AND MANAGEMENT - Mackevičius, Jonas; Ragauskienė, Erika (Ekonomika, 2012)
State property serves as an essential provision for ensuring the improvement of society‘s quality of life, the growth of economic welfare, social security, political stability and cohesive development in all facets of life. The purpose of the article is to analyze the current variety of property classifications, to perform an analysis of state property values and their management system. When transforming the state property management system towards a higher level of effectiveness, it is necessary to perform a comprehensive state property valuation which would fully reflect the structure of state property in both a quantitative and a value sense.